Agrobacterium mediated transformation of plantain (Musa spp.) cultivar Agbagba - Tripathi, L.; Tripathi, J.N.; Hughes, J.D. (2005)
An Agrobacterium-mediated plant transformation system was developed for the production of transgenic plantain [Musa spp. cultivar Agbagba (AAB)]. Apical shoot tips were transformed using Agrobacterium strain EHA105 with the binary vector pCAMBIA 1201, having the hygromycin resistancegene as a selection marker and GUS-INT as a reporter gene. Transient expression of the bglucuronidase (uid A) gene was achieved in transformed apical shoot tips. The hygromycin resistant shoots were regenerated 4 to 5 weeks after co-cultivation of explants with Agrobacterium. The two stepselection procedure allowed the regeneration of shoots which were uniformly transformed. The integration of the uid A gene was confirmed by polymerase chain reaction (PCR) and Southern blot analysis. In this study, transformation based on regeneration from apical shoot tips has beendemonstrated. This process does not incorporate steps using disorganized cell cultures but uses micropropagation, which has the important advantage that it allows regeneration of homogeneous populations of plants in a short period of time. This study shows the enormous potential for genetic manipulation of Musa species for disease and pest resistance, as well as abiotic factors, using a rapid and non-species specific transformation and regeneration system.